EVALUATION OF HEAVY METALS LOADING OF RIVERS GANGA AND YAMUNA IN - AVANTIKA PANDEY; P.W RAMTEKE; O.P VERMA (International Journal of Pharma and Bio Sciences, 2013)
The concentration of Chromium(Cr),Copper(Cu),Iron(Fe),Nickel(Ni), Lead (Pb)and Zinc(Zn). Which may effect human health and the health of the aquatic ecosystem were determined in the rivers Ganga and Yamuna on seven sampling stations at Allahabad using Atomic absorption Spectrophotometer, Spectra AA 220 G,Varian pvt. Ltd, Hyderabad. The levels of the heavy metals were compared with BIS, 2005 and WHO, 1993. All the heavy metals at all the sampling stations were found above the permissible limits. The concentration of these heavy metals in the study area indicated that the river is highly polluted. The possible sources of these heavy metal pollutions are diverse: originating from natural or anthropogenic sources and point sources.